An Africana Philosophy of Temporality Homo Liminalis - Sawyer, Michael E. (Springer International Publishing, 2018)
This book is a timely intervention in the areas of philosophy, history, and literature. As an exploration of the modern political order and its racial genealogy, it emerges at a moment when scholars and activists alike are wrestling with how to understand subject formation from the perspective of the subordinated rather than from dominant social and philosophical modes of thought. For Sawyer, studying the formation of racialized subjects requires a new imagining of marginalized subjects. Black subjectivity is not viewed from the static imaginings of social death, alienation, ongoing abjection, or as a confrontation with the treat of oblivion. Sawyer innovates the term "fractured temporality," conceptualizing Black subjects as moving within and across temporalities in transition, incorporated, yet excluded, marked with the social death of Atlantic slavery and the emergent political orders it etched, and still capable of exerting revolutionary force that acts upon, against, and through racial oppression.